A Stage 4 Hepatoid Adenocarcinoma of the Endometrium: a Case Report and Review of Literature - Duygu Altin; Ayca Kirmizi; Cevriye Cansiz Ersoz; Salih Taskin; Bulent Berker; Firat Ortac (Medical Network, 2018)
We report a case of 72-year-old woman who was hospitalized with vaginal bleeding and abdominal pain. Magnetic resonance imaging showed tumor both in endometrial cavity and ovaries with multiple distant metastasis. Her serum alpha-fetoprotein level was >54000 ng/mL. Total abdominal hysterectomy with bilateral salpingo-oophorectomy, total omentectomy, appendectomy, bilateral pelvic and paraaortic lymph node dissection, a 20 cm ileal resection with ileal anastomosis, metastasectomy were performed and peritoneal washing was obtained. The pathologic diagnosis was endometrial hepatoid adenocarcinoma. Because of her poor medical condition, she received only palliative chemotherapy. After two days of 5-fluorouracil she died within 2 months. Hepatoid adenocarcinomas are extrahepatic neoplasms that exhibit features of hepatocellular carcinoma. It was first reported as gastric neoplasm but is seen in many different organs and its frequency is increasing. To date only 11 cases of hepatoid adenocarcinoma of the endometrium were reported. It has a poor prognosis and there isn't an effective treatment yet.